2019
DOI: 10.25248/reas.e1410.2019
|View full text |Cite
|
Sign up to set email alerts
|

Atenção à Saúde da População LGBT numa capital nordestina

Abstract: Objetivo: Identificar, a partir da compreensão de gestores e profissionais de saúde, as dificuldades e desafios, potencialidades e facilidades encontradas na Atenção à Saúde Integral de Lésbicas, Gays, Bissexuais, Travestis e Transexuais, no município do Recife. Métodos: É uma pesquisa de natureza exploratória, com metodologia qualitativa, realizada com entrevistas semiestruturadas, colhidas de gestores e profissionais de quatro estabelecimentos de saúde que direcionam ações voltadas para população LGBT, tanto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
(4 reference statements)
0
3
0
2
Order By: Relevance
“…Corroborando os relatos, alguns estudos apontaram que os profissionais de saúde se mostraram inquietos em relação à escassez e à ausência da temática na formação em saúde e às dificuldades de acesso às informações inerentes às particularidades de saúde das lésbicas 40,41 . Já a pesquisa de Dorsen et al 42 evidenciou que as enfermeiras se sentem mais confortáveis em cuidar de lésbicas quando, na formação acadêmica, lhes foram proporcionadas reflexões acerca da diversidade sexual e de gênero e seu impacto na saúde.…”
Section: Na Faculdade Nunca Foi Falado Até Porque é Uma Coisa Bem Mai...unclassified
“…Corroborando os relatos, alguns estudos apontaram que os profissionais de saúde se mostraram inquietos em relação à escassez e à ausência da temática na formação em saúde e às dificuldades de acesso às informações inerentes às particularidades de saúde das lésbicas 40,41 . Já a pesquisa de Dorsen et al 42 evidenciou que as enfermeiras se sentem mais confortáveis em cuidar de lésbicas quando, na formação acadêmica, lhes foram proporcionadas reflexões acerca da diversidade sexual e de gênero e seu impacto na saúde.…”
Section: Na Faculdade Nunca Foi Falado Até Porque é Uma Coisa Bem Mai...unclassified
“…In theoretical activities of LASFC-FITS, which made it possible to learn about the theme exposed in the present work, the impact of the creation of specialized outpatient clinics for the LGBTQIA+ population on the social body was perceptible, thus arousing the interest of the members of the League in understanding and experience the reality of such a group, thus being able to obtain enrichment in terms of personal and academic experience. This way, the starting point was built and consolidated in the LGBT Outpatient Clinic of Jaboatão dos Guararapes, a service chosen mainly because it is included in the state of Pernambuco, which is a national reference in terms of health care for the LGBTQIA+ population (DE LIMA et al, 2019).…”
Section: The Starting Pointmentioning
confidence: 99%
“…Pernambuco is a national reference in terms of health care for the LGBTQIA+ population (DE LIMA et al, 2019), so we identified the possibility of service users benefiting and impacting through the participation of LASFC-FITS members in medical care, according to the supervision of the service doctor, for example. Such consultations were of great importance for strengthening the clinic, as there are still limitations regarding the resources available for the implementation of the office.…”
Section: Initial Questionsmentioning
confidence: 99%
“…Corroborating the reports, some studies showed that health professionals were concerned about the scarcity and absence of the topic from health education and/or the difficulties in accessing information inherent to lesbians' health particularities 40,41 . The study by Dorsen et al 42 showed that nurses feel more comfortable in caring for lesbians, when in their academic training they were provided with reflections on sexual and gender diversity and their impact on health.…”
Section: Nursing Training For Lesbian Health Carementioning
confidence: 99%